The Role of National Resilience in Maintaining State Stability in the Transformation of Global Society - Aditya Nur Pratama; Afif Raihan Putra Purnama (Konsultan Jurnal Ilmiah Indonesia, 2026)
The transformation of global society triggered by the development of digital technology, geopolitical changes, and increasing interdependence between countries has created various multidimensional threats to national stability. National resilience no longer relies solely on military strength, but demands synergy between ideological strength, quality of human resources, digital literacy, technological capabilities, and the effectiveness of the state apparatus in maintaining security and order. This study aims to analyze how national resilience plays a role in maintaining national stability in the era of global societal transformation by reviewing the contributions of ideology, technology, human resources, law, and digital security factors. The method used is a literature review by examining scientific articles published between 2020 and 2025 through Google Scholar, Garuda, DOAJ, and CrossRef. The results of the analysis show that national resilience is significantly influenced by the state's ability to manage digital challenges such as cyberattacks, disinformation, and the decline of national identity, as well as global dynamics such as geopolitical competition and global economic pressures. Strengthening Pancasila values, digital literacy of the younger generation, defense modernization, adaptation of legal policies, and increasing the capacity of the apparatus are determining factors in maintaining national stability. This study concludes that national resilience must be built through a multidimensional, adaptive, integrative, and long-term approach to enable Indonesia to sustainably address global change.